2018
DOI: 10.1186/s40560-018-0331-7
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of sedation depth in intensive care unit by therapeutic drug monitoring? A prospective observation study of medical intensive care patients

Abstract: BackgroundAnalgosedation is a cornerstone therapy for mechanically ventilated patients in intensive care units (ICU). To avoid inadequate sedation and its complications, monitoring of analgosedation is of great importance. The aim of this study was to investigate whether monitoring of analgosedative drug concentrations (midazolam and sufentanil) might be beneficial to optimize analgosedation and whether drug serum concentrations correlate with the results of subjective (Richmond Agitation-Sedation Scale [RASS]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
2
15
1
2
Order By: Relevance
“…This appears to be high compared to previous investigations [ 17 19 ]. Our median plasma concentration is comparable to the finding by Nies et al They observed a median midazolam concentration of roughly 1500 µg/L for RASS -5 [ 20 ]. The difference in median concentrations are probably due to the fact that on the one hand, the study by Bremer et al included post-operative ICU patients and the study by Oldenhof et al included only 17 patients, and on the other hand that the study by Nies et al included more long term severe ICU patients.…”
Section: Discussionsupporting
confidence: 89%
“…This appears to be high compared to previous investigations [ 17 19 ]. Our median plasma concentration is comparable to the finding by Nies et al They observed a median midazolam concentration of roughly 1500 µg/L for RASS -5 [ 20 ]. The difference in median concentrations are probably due to the fact that on the one hand, the study by Bremer et al included post-operative ICU patients and the study by Oldenhof et al included only 17 patients, and on the other hand that the study by Nies et al included more long term severe ICU patients.…”
Section: Discussionsupporting
confidence: 89%
“…Intravenous continuous infusions may be indicated when seizures persist under a maximal treatment: therapeutic options include midazolam or lidocaine [124]. Despite pediatricians' concern on midazolam (MID) use in spontaneously breathing infants, due to the risk of respiratory failure, midazolam may be started with a loading dose and then clinically titrated to effect: its advantages are the rapid metabolic inactivation, clearance and comparatively short elimination half-time [125]. A therapeutic range is not used in the clinical practice.…”
Section: Tdm and Antiepileptic Drugsmentioning
confidence: 99%
“…The literature reports a weak drug–response relationship in both inhalational and intravenous sedative agents, partly attributed to polypharmacy and the high pathophysiological heterogeneity of mechanically ventilated patients [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number of observations per patient was 1019 ± 430, 852 ± 797, and 1158 ± 436 for the isoflurane, sevoflurane, and desflurane groups. The duration of sedation per group in rounded hours was comparable across groups: 18 [16][17][18][19][20][21]; 17 ; 18 [15][16][17][18][19][20][21][22] for isoflurane, sevoflurane, and desflurane, respectively (p = 0.71).…”
Section: Number Of Measurementsmentioning
confidence: 92%